The Influence Of Tax Rates, Tax Understanding, And Tax Sanctions On Taxpayers Compliance With Small And Medium Enterprises (MSME) - Islamey, Avisa Kinantan Nahdah; Muslimin, Muslimin (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2024)
Taxation is one of the main focuses of the government to increase state revenue. Tax is a form of mandatory contribution to the state owed by individuals or entities that are compelling based on the law. The results of these revenues are used to realise development and state spending. Therefore, paying taxes is an obligation for every taxpayer to participate in national development. One of the tax sectors that contributes to state revenue is the Micro, Small and Medium Enterprises (MSME) sector. Therefore, MSME taxpayer compliance must continue to be improved. The purpose of this study was to examine the effect of tax rates, tax understanding, and tax sanctions on MSME taxpayer compliance. This research uses quantitative research. The data used is primary data with multiple linear regression analysis techniques and processed using SPSS software. The data was obtained by distributing questionnaires directly to each respondent. The sampling technique used purposive sampling. The sample criteria for this study are MSMEs that have an NPWP as many as 44 MSME. The results of this study indicate that tax understanding and tax sanctions have a positive and significant effect on MSME taxpayer compliance, while tax rates have a negative and insignificant effect on MSME taxpayer compliance